(untitled) (CIPEEX, 2026)
Summary Introduction: Human milk contains 87% water and 13% nutrients essential to child development. Breastfeeding promotes maternal health and bond, but diseases such as obesity, diabetes, hypertension and hypothyroidism can change its nutritional composition. There are still few studies on the impact of these conditions on the energy value of milk. Objective: To correlate the presence of chronic diseases (obesity, hypertension, diabetes and hypothyroidism) in donor lactating women with the energy content of human milk. Method: Observational, quantitative and cross-sectional study conducted in a Human Milk Bank in Goiás, between June 2024 and June 2025. The energy value of milk was evaluated through crematocrit, comparing donors with chronic and healthy diseases. The data were extracted from records and medical records, following ethical standards. Results: 34 donors were included, 5 with comorbidities. The average milk energy was 551.2 kcal/L. Donors with controlled diabetes and hypothyroidism had high values; those with hypertension had the lowest value. Controlled obesity showed little variation. Conclusions: Chronic diseases can influence the energy value of human milk, although they are not the only factors involved. The study contributes as a basis for future research with larger samples. Keywords: breastfeeding; chronic diseases; human milk. Introduction Human milk (LH) is composed mainly of water (87%), ensuring adequate hydration to the infant, and by essential nutrients (13%) distributed in carbohydrates, lipids and proteins, which contribute to child growth and development. Lactose, the main carbohydrate of LH, provides energy and favors the absorption of minerals, while proteins and fats provide important immunological and caloric elements. Breastfeeding is fundamental to the baby’s health, preventing diseases and promoting physical and neurological development, in addition to strengthening the mother-baby bond. However, maternal conditions such as obesity, diabetes, hypertension and hypothyroidism can change the composition of milk, affecting levels of macronutrients, hormones and nutritional quality. Hypothyroidism, for example, can reduce milk production and ejection, while diabetes changes the concentrations of glucose, lactose, fat and proteins, and hypertension increases immune proteins in milk. Studies show that these chronic maternal diseases significantly modify the nutritional composition of LH, although there is still a shortage of research on its direct impact on the energy value of milk. MATERIALS AND METHODS This is an observational, quantitative and cross-sectional study conducted in a Human Milk Bank (HLB) in Goiás, which analyzed samples of milked and donated milk between June 2024 and June 2025, focusing on comparing the energy content of milk from donors with chronic diseases (obesity, diabetes, hypertension and hypothyroidism) with that of healthy donors. Secondary data extracted from standardized BLH records and medical records were used, and samples with inadequate physicochemical conditions or that suffered accidents during pasteurization were excluded. The crematocrit, which indicates the concentration of fat and, therefore, the energy value of milk, was obtained following the Fiocruz protocol, through the centrifugation of samples and measurement of the cream column. The information was organized in an Excel spreadsheet with clinical data of donors and their children. The study was approved by the Ethics Committee of UniEVANGÉLICA and followed the Brazilian standards of research with human beings. RESULTS During the collection period, the medical records of 34 regular donors from a Human Milk Bank were analyzed, in order to evaluate the impact of chronic maternal diseases on the energy value of human milk, measured through pre-pasteurization crematocrit. The overall average was 551.2 kcal/L, being 552.8 kcal/L among healthy donors and 542.4 kcal/L among five donors with chronic conditions (two with obesity, one with diabetes, one with hypertension and one with hypothyroidism). The two donors with obesity had averages of their crematocrits of 521.2 kcal/L and 544 kcal/L, values close to the general average, suggesting that, although there are metabolic changes associated with obesity, the maternal body can maintain milk production with adequate energy value, especially in cases of controlled obesity. The donor with hypothyroidism had an average of 626 kcal/L, above the general average, indicating that, if well controlled, hypothyroidism may not compromise the energy content of milk, despite its potential effects on the synthesis of lipids and proteins. The sample of the hypertensive donor was the one with the lowest energy value (399 kcal/L), revealing possible negative interference of hypertension in the concentration of milk fat, a fact corroborated by the literature. On the other hand, the donor with controlled diabetes mellitus had the highest values (average of 723 kcal/L), indicating that glycemic control can lead to changes in the lipid composition of milk and an increase in its caloric value. In summary, although the number of donors with comorbidities is reduced, the data indicate that certain chronic diseases, especially when not well controlled, can impact the energy value of human milk, while others, under adequate control, do not necessarily cause significant nutritional damage to the infant. Conclusion The research allowed a detailed analysis of the energy value of donated human milk and the health conditions of donors, contributing to the guarantee of the quality of milk destined for infants. Although the incidence of chronic diseases among the participants was low, the results indicate that these conditions can influence the crematocrit, but they are not the only factors involved, pointing to the need for additional studies. The main limitation was the interruption of milk processing in the unit due to technical problems, which significantly reduced the sample. Still, the data showed that the milk provided to premature infants in the analyzed unit has adequate energy value, and the authors intend to use this study as a pilot for future research with larger samples. THANKS The authors thank the National Council for Scientific and Technological Development (CNPq), the Evangelical University of Goiás (UniEVANGÉLICA) and the Research Support Foundation of the State of Goiás (FAPEG) for the support that made this study possible.